Pelatihan Physics Virtual Experiment Sebagai Solusi Praktikum Fisika Pada Masa Pandemi - Syafira Setya Putri; Siti Nur Khotimah; Muhammad Rayvan; Yosi Oktaviani; Irnin Agustina Dwi Astuti (Jurnal PkM Pengabdian kepada Masyarakat, 2021)
In Online learning carried out today due to the Covid 19 Pandemic is an obstacle for students and teachers in practicum activities. Practicum activities that are usually carried out face-to-face in the laboratory become stopped and cannot be done. Therefore, a solution is needed to keep the practical activities of physics running. One of them is by using a physics practicum with crocodile physics. Raising the above issues, then our PKM-PM Team conducted community service activities in the form of Virtual Experiment Physics Training using Crocodile Physics which was carried out at Sma Negeri 3 Jakarta school. The implementation methods used are socialization, training and mentoring. The result of this training is to create a simulation of the physics practicum itself using Crocodile Physics.  This activity gets a positive response based on knowledge needs. By using this virtual practicum has been able to provide knowledge benefits to the physics learning process. This training becomes a reference for trainees to carry out practicum activities virtually in online learning today.